Delegating National Security - Knowles, Robert (2021)
Conservative scholars and a Supreme Court majority support reviving the nondelegation doctrine as a way to downsize the administrative state. But proposals from these scholars and Justices inevitably maintain there should be an exception for national security. This Article explains why a national security exception defeats the nondelegation doctrine’s goals of preserving the separation of powers and individual liberty. In doing so, this Article charts the ways the national security state regulates and accounts for its immunity from the harshest attacks on the administrative state. This Article also predicts how this dynamic would affect a nondelegation revival. This Article begins by offering a new model depicting agency lawmaking in national security. It draws on insights from military-industrial complex theory, which has received scant attention from legal scholars. What I call the military-administrative complex uses threat-inflation to obtain increased regulatory authority over individuals, including American civilians. As its reach expands, the boundary between domestic and national security regulation fades. Next, this Article describes why presidential control theory—which grounds the legitimacy of delegation in the President’s political accountability and oversight—cannot justify a national security exception. The military-administrative complex is so entrenched and insulated that even the President must delegate vast discretion to agencies within it. Finally, this Article scrutinizes the sources the Justices themselves cite to support their nondelegation arguments. If the Court adopted the reasoning in these sources, this Article predicts, a revived nondelegation doctrine with a national security exception would be inherently unstable. Ever-expanding definitions of “national security” could allow the exception to swallow the rule